2013
DOI: 10.3174/ajnr.a3423
|View full text |Cite
|
Sign up to set email alerts
|

Brain Injury Patterns in Hypoglycemia in Neonatal Encephalopathy

Abstract: BACKGROUND AND PURPOSE:Low glucose values are often seen in term infants with NE, including HIE, yet the contribution of hypoglycemia to the pattern of neurologic injury remains unclear. We hypothesized that MR features of neonatal hypoglycemia could be detected, superimposed on the predominant HIE injury pattern.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
62
1
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(69 citation statements)
references
References 16 publications
1
62
1
5
Order By: Relevance
“…Because of the complexity of a newborn's circumstances, other factors that may dispose to brain injury, such as asphyxia, premature birth, low birth weight and maternal factors complicated the clinical case study. However, in 10 cases with MRI anomalies, all showed occipital white matter damage, consistent with hypoglycemic injury to susceptible parts of the brain mentioned in the literature (16,23); therefore, it was considered these MRI changes were mainly induced by hypoglycemia. Previous studies have reported that structural and functional cortical abnormalities in patients with infantile spasms have a predilection for posterior brain areas (32,33).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Because of the complexity of a newborn's circumstances, other factors that may dispose to brain injury, such as asphyxia, premature birth, low birth weight and maternal factors complicated the clinical case study. However, in 10 cases with MRI anomalies, all showed occipital white matter damage, consistent with hypoglycemic injury to susceptible parts of the brain mentioned in the literature (16,23); therefore, it was considered these MRI changes were mainly induced by hypoglycemia. Previous studies have reported that structural and functional cortical abnormalities in patients with infantile spasms have a predilection for posterior brain areas (32,33).…”
Section: Discussionmentioning
confidence: 96%
“…However, few large systematic studies have been conducted to characterize the association of neonatal hypoglycemic brain injury with infantile spasms. The lack of glucose can selectively impair multiple brain regions, including the superficial cortex, dentate gyrus, hippocampus, and caudate putamen; this impairment occurs through several putative mechanisms, such as the release of excitatory neurotransmitter (19), increased mitochondrial free radical generation and initiation of apoptosis (20), activation of neuronal nicotinamide adenine dinucleotide phosphate (NADPH) oxidase (21), and altered cerebral energetic characteristics (22,23). In one study in which the etiology of remote symptomatic epilepsy with onset during the first 3 years of life was examined, it was observed that neonatal hypoglycemia was the most common etiology, and infantile spasms were the most common type of seizure (14).…”
Section: Discussionmentioning
confidence: 99%
“…19,20 This mechanism could explain the observation that the watershed pattern of injury on magnetic resonance imaging (MRI) is common among infants with HIE who also have very low blood glucose concentrations (<1.5mmol/L). 21 However, hypoglycaemia and watershed hypoperfusion may be epiphenomena, as discussed below.Conventional electroencephalography (EEG) shows that electrographic seizures occur in one-half to two-thirds of infants with moderate to severe HIE. [22][23][24] The effect of seizures on cerebral energy metabolism and glucose has been reviewed by Volpe,25 who highlights that accelerated energy utilization and rapid depletion of cerebral glucose stores occurs during seizures, and points out that, under conditions of limited supply (i.e.…”
mentioning
confidence: 99%
“…When compared with early glucose measurements, this radiological hypoglycaemia was associated with clinical hypoglycaemia (defined as one or more blood glucose measurements of <2.6mmol/L) with reasonable accuracy (positive predictive value of 83%, negative predictive value of 76%). 21 The authors discussed a number of limitations to the study, not least the lack of standardization of glucose measurements, and they made assumptions about radiological hypoglycaemia that may have been be overly stringent. 50 However, these aspects of design do not detract from the observation that the lowest mean blood glucose concentration in the 'clinical hypoglycaemia' group was 1.6mmol/L (SD 0.7mmol/L): many of the values in this range are not known to be associated with brain injury in healthy, term-born infants.…”
mentioning
confidence: 99%
See 1 more Smart Citation